The Double Power Law in Consumption and Implications for Testing Euler Equations - Toda, Alexis Akira; Walsh, Kieran (Journal of Political Economy, 2015)
We provide evidence suggesting that the cross-sectional distributions of US consumption and its growth rate obey the power law in both the upper and lower tails, with exponents approximately equal to four. Consequently, high-order moments are unlikely to exist, and the generalized method of moments estimation of Euler equations that employs cross-sectional moments may be inconsistent. Through bootstrap studies, we find that the power law appears to generate spurious nonrejection of heterogeneous-agent asset pricing models in explaining the equity premium. Dividing households into age groups, we propose an estimation approach that appears less susceptible to fat tail issues.